Education as a catalyst towards realising the development goals of Malaysia: case study of the east coast economic study OF THE EAST COAST ECONOMIC REGION - Siwar, Chamhuri; Abdulai, Abdul-Mumin (2011)
As contained in her national development mission, Malaysia is expected to become a developed and high income economy by 2020. A mission favourably referred to as the Vision 2020. The realisation of such a noble goal will not come on a silver platter. Perhaps this awareness underscores the identification of certain sectors of the economy by the Malaysian government as key to achieve this development target. And education, to generate innovative knowledge for sustained economic growth, is one of the sectors. To achieve the status of a developed economy can be hard, especially in the midst of deep-seated development disparities among regions in the economy. Removing development imbalances among regions is believed to have positive impact on long-term economic growth. It also reduces income inequalities among citizens and increases their livelihood chances, thereby leading to higher living standards. For this reason, the Malaysian government has adopted a regional development approach, which seeks to correct regional development imbalances for accelerated and sustained development. This paper examines one such region—the east coast economic region (ECER)--where education has been seen as one of the important sectors to bridge the development gap between this underdeveloped region and the other relatively developed regions in Malaysia.